Follow-Up of Women with Cervical Cytological Abnormalities: Progression and Regression Events - dos Santos, Aniúsca Vieira (Asian Pac J Cancer Prev, 2019)
SECTION TITLE: Abnormalities in the cervix, when identified early by Pap smear, can be treated in the early stages or in the precursor stages of the neoplasia, which may increase the chances of regression of the lesion. The aim to verify the rate of cervical abnormalities and to evaluate the risk of progression or regression associated with age and cytological diagnosis. METHODS: The study was conducted in a referral hospital in Southern Brazil, based on the results of pathology and cytopathology laboratory tests of uterine cervix. The historical cohort included patients with an abnormal cytology diagnosis in the period from January 2010 to December 2014, followed until July 2016. RESULTS: A total of 42,389 cervical smears were analyzed, 4,427 of which were eligible for analysis of the evolution of cervical abnormalities. In progression and regression events analysis, we observed that patients with a cytological diagnosis of atypical glandular cells presented a higher risk of cervical abnormality progression (Hazard Ratio: 2.0 and 95% confidence intervals 1.36–3.48). We also observed that patients younger than 25 years old were more likely to regress the cervical lesions (Hazard Ratio:1.4 and 95% confidence intervals 1.20–1.74). CONCLUSIONS: The associations found between the events (progression and regression), age and cytological diagnosis, highlights the importance of cytological screening in populations at risk of precursor of cervical cancer lesions, especially in women older than 25 years.